Association of the TGrI29 microsatellite in thyroglobulin gene with autoimmune thyroiditis in a Argentinian population: a case–control study - Varela, Viviana (2010)
Autoimmune thyroid disease (AITD) is a multifactorial disorder that involves a putative association with thyroid autoantigen-specific and immune regulatory genes, as well as environmental factors. The thyroglobulin gene is the main identified thyroid autoantigen-specific gene associated to autoimmune thyroiditis. The aim of this work was to test for evidence of allelic association between autoimmune thyroiditis (AT) and thyroglobulin polymorphism markers in Argentinian patients. We studied six polymorphisms distributed throughout all the thyroglobulin gene: four microsatellites (Tgms1, Tgms2, TGrI29, and TGrI30), one insertion/deletion polymorphism (IndelTGIVS18), and one exonic single nucleotide polymorphism (c.7589G>A) in 100 AT patients and 100 healthy control subjects. No differences in allele and genotype frequencies distribution were observed between autoimmune thyroiditis cases and controls for Tgms1, Tgms2, TGrI30, IndelTGIVS18, and c.7589G>A. However, when we analyzed autoimmune thyroiditis patients with the TGrI29 microsatellite we found a significant association between the 197-bp allele and autoimmune thyroiditis (33.50% vs. 19.00% in control group) (P = 0.001). In addition, a significant major prevalence of the 197/201-bp genotype has been also seen in autoimmune thyroiditis subjects (59% vs. 24% in control group, P<0.0001). In conclusion, our work showed the association between the thyroglobulin gene and autoimmune thyroiditis in Argentinian population and supports the described evidence of thyroglobulin as a thyroid-specific gene linked to AITD.